Photoaffinity labelling of steroid-hormone-binding glutathione S-transferases with [3H]methyltrienolone. Inhibition of steroid-binding activity by the anticarcinogen indole-3-carbinol. - Danger, D P (1992)
The identification and characterization of steroid-hormone-binding glutathione S-transferases (GST) were undertaken using photoaffinity-labelling techniques. Irradiation of mouse liver cytosol, in the presence of 50 nM-[3H]methyltrienolone, resulted in the specific affinity labelling of five proteins. One of these proteins, designated MBP27, had an approximate molecular mass of 27 kDa under denaturing conditions and was induced by treatment of mice with either 2(3)-t-butyl-4-hydroxyanisole (BHA) or phenobarbital (PB). An additional affinity-labelled protein, MBP25, which was not detected in untreated mouse cytosol, was induced in the liver cytosols from BHA- and PB-treated mice. The molecular masses of these proteins and their induction by BHA and PB suggested that they may be steroid-hormone-binding GST subunits. Irradiation of mouse liver cytosol in the presence of [3H]methyltrienolone, followed by immunoprecipitation using GST-specific antibodies established that both GST mu and GST alpha bind [3H]methyltrienolone and both contribute to the affinity-labelled protein designated MBP27. GST Ya1 Ya1, an alpha class GST that is not expressed in untreated mouse liver but is induced by BHA and PB, was also found to bind [3H]methyltrienolone and is identical with the affinity-labelled protein designated MBP25. Experiments were undertaken next to assess the effects of the anticarcinogenic plant compound indole-3-carbinol (I3C) on GST-mediated steroid hormone-binding using the photoaffinity labelling techniques. Treatment of mice with I3C resulted in the induction of immunoreactive GST mu and GST Ya1 Ya1. However, the steroid-binding activity of these proteins in vitro was severely inhibited by the acid-condensation products of I3C that are generated in the stomach after ingestion. These results suggest that I3C may inhibit GST-mediated steroid-binding activity which could contribute to the anticarcinogenic activity of this compound.